Intraoperative Management of the Recurrent Laryngeal Nerve Transected or Invaded by Thyroid Cancer - Masuoka, Hiroo; Miyauchi, Akira (Frontiers in Endocrinology, 2022)
Thyroid cancer often invades the recurrent laryngeal nerve (RLN), causing vocal cord paralysis. In such patients, the invaded portion of the RLN usually needs to be resected through curative surgery. We attempt to preserve the nerve by performing sharp dissection in such cases. During nerve dissection, an intraoperative nerve monitoring system helps identify the course of the RLN in the fibrous tissue around the tumor or even within the tumor, and also helps evaluate the nerve integrity. Because of extensive dissection, the preserved RLN may become much thinner than its original thickness. We refer to this procedure as “partial layer resection” of the RLN. In our cases, although the dissected RLNs became thinner, we found that vocal cord function recovered in most patients. If the RLN is fully involved by thyroid cancer or response of the vocal cord against electric stimulation to the RLN is lost, we resect the portion of the RLN together with the tumor and repair it using one of the reconstruction techniques. When a unilateral RLN is resected, the vocal cord on that side is paralyzed. Symptoms include hoarseness, mis-swallowing, and short phonation. RLN reconstruction using one of the reconstruction techniques leads to the recovery of phonatory and swallowing function, although the normal motion of the vocal cord on the side of the anastomosis is not restored. We used direct anastomosis, free nerve grafting, ansa cervicalis-RLN anastomosis, and vagus-RLN anastomosis to reconstruct the RLN. Thyroid cancer often invades the RLN near the Berry’s ligament. In such patients, surgeons might assume that reconstruction of the RLN may not be possible because the peripheral stump of the RLN cannot be observed. However, if we divide the inferior pharyngeal constrictor muscles along the lateral edge of the thyroid cartilage, the peripheral RLN can be identified, and nerve reconstruction can be performed. We refer to this procedure as “laryngeal approach”. In summary, of the patients with thyroid cancer who required resection of the RLN, RLN reconstruction led to the recovery of phonatory function. We suggest that all thyroid surgeons familiarize themselves with these reconstruction techniques.